An investigation into the relationship between creativity and academic performance in school children - Noble, Sybil (Rhodes University, Faculty of Humanities, Department of Psychology, 1970)
The subject of creativity is of interest not only to the research worker and educationist but also, with its related mental health aspect, to the clinical psychologist. As the writer's interest is in clinical psychology the opportunity, which occurred in 1968, to undertake research on creativity, was welcomed. This opportunity arose out of a larger piece of research into the relationships between personality variables and mathematical ability in school children. This involved the administration of personality tests and tests of arithmetic and mathematical ability to all the English speaking school children in Grahamstown from Standard 2 to Standard 10. The writer assisted in this testing program and did the greater part of the marking, scoring and entering on computer sheets. Thus personality test scores for over 2,000 children from the age of 8 or 9 to 17 or 18, both boys and girls were available. It was found possible to extend the computer program to calculate a score for creativity based on a combination of Cattell's personality factors and it was decided to compare these creativity scores with actual school performance, as measured by internal school examinations, which with the cooperation and agreement of the Cape Education Department and local schools, the writer was able to obtain. Intro., p.1.
Keywords: Creative ability; Academic achievement; Performance in children